2017
DOI: 10.12688/wellcomeopenres.11135.1
|View full text |Cite
|
Sign up to set email alerts
|

PARV4 prevalence, phylogeny, immunology and coinfection with HIV, HBV and HCV in a multicentre African cohort

Abstract: Background: The seroprevalence of human parvovirus-4 (PARV4) varies considerably by region. In sub-Saharan Africa, seroprevalence is high in the general population, but little is known about the transmission routes or the prevalence of coinfection with blood-borne viruses, HBV, HCV and HIV.  Methods: To further explore the characteristics of PARV4 in this setting, with a particular focus on the prevalence and significance of coinfection, we screened a cohort of 695 individuals recruited from Durban and Kimberl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…A previous study of HBV serology in adults in the same setting found HBsAg prevalence of 9.5% (55/579) (4). Children were recruited as part of the C o-infection in S outh- A frican C hildren (‘COSAC’) study as previously described (19,20). The lower age limit of recruitment was 6 months in order to limit the detection of maternal anti-HBs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study of HBV serology in adults in the same setting found HBsAg prevalence of 9.5% (55/579) (4). Children were recruited as part of the C o-infection in S outh- A frican C hildren (‘COSAC’) study as previously described (19,20). The lower age limit of recruitment was 6 months in order to limit the detection of maternal anti-HBs.…”
Section: Methodsmentioning
confidence: 99%
“…Children were recruited as follows: HIV-negative children age 6-60 months (n=174), recruited through the Kimberley Respiratory Cohort (KReC) as previously described (19). These children were admitted to hospital between July 2014 and August 2016 with a clinical diagnosis of respiratory tract infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk increases in males, due to more interaction with other individuals from their troop and other troops, and higher levels of dispersal than females (Kitchen et al, 2004; Rose, 1994). Attempts at species management can also influence pathogen presence by influencing levels of stress, immunosuppression, interaction with other host species, changes in social habits, and clustering of individuals (Sharp et al, 2017). Although there are no direct comparative studies between free-range and captive OWP, high prevalences to PARV4 and HBoV have been reported in OWP maintained in captivity (Kapoor et al, 2010; Sharp et al, 2010).…”
Section: Introductionmentioning
confidence: 99%